Feminismos, pensamiento crítico y propuestas alternativas en América Latina. - Valdivieso Ide, Magdalena; Sagot Rodríguez, Montserrat (CLACSO, 2017)
The different works gathered here make contributions from the feminist perspective to the construction of alternatives in Latin America and the Caribbean, and position feminism as an unavoidable form of critical thinking. The texts show how feminism serves as an analytical tool to address macrosocial and intersectional problems, but also to think about local realities. The compilation is also a reflection of the interdisciplinary work promoted by the CLACSO Working Groups that seeks to produce relevant knowledge to understand and help transform reality.